Differential selection on pollen and pistil traits in relation to pollen competition in the context of a sexual conflict over timing of stigma receptivity. (18th August 2015) - Lankinen, Åsa; Strandh, Maria
Abstract : Sexual conflict and its evolutionary consequences are understudied in plants, but the theory of sexual conflict may help explain how selection generates and maintains variability in both plants and animals. Here, we show that pollen and pistil traits involved in a sexual conflict over timing of stigma receptivity are differentially advantageous during pollen competition depending on stage of floral development and varying pollen deposition schedules. Variation in success of these traits over floral development time may result from sexually antagonistic selection. Abstract: Sexual conflict and its evolutionary consequences are understudied in plants, but the theory of sexual conflict may help explain how selection generates and maintains variability. Here, we investigated selection on pollen and pistil traits when pollen arrives sequentially to partially receptive pistils in relation to pollen competition and a sexual conflict over timing of stigma receptivity in the mixed-mating annual Collinsia heterophylla (Plantaginaceae). In this species the conflict is generated by early fertilizing pollen that reduces seed production, which is counteracted by delaying receptivity in the recipient. We performed sequential two-donor pollinations at early floral developmental stages involving two pollen deposition schedules (with or without a time lag of 1 day), using only outcross or self and outcross pollen. We investigated pollen and pistil traits in relation to siring success (male fitness) and seed production (female fitness). In contrast to previous findings in receptive pistils in C. heterophylla and in other species, last arriving pollen donors showed highest siring success in partially receptive pistils. The last male advantage was weaker when self pollen was the first arriving donor. Two measures of germination rate (early and late) and pollen tube growth rate of first arriving donors were important for siring success in crosses with a time lag, while only late germination rate had an effect in contemporary crosses. Curiously, late stigma receptivity was negatively related to seed production in our contemporary crosses, which was opposite to expectation. Our results in combination with previous studies suggest that pollen and pistil traits in C. heterophylla are differentially advantageous depending on stage of floral development and varying pollen deposition schedules. Variation in success of these traits over floral development time may result from sexually antagonistic selection.